Risiko Pendapatan Usahatani Padi Sawah (Kasus Desa Noelbaki, Kecamatan Kupang Tengah, Kabupaten Kupang, NTT) - Hakim, Shesy A.; Pellokila, Marthen R.; Nampa, I Wayan (University of Islam Malang, 2021)
Farming is one of the industries most susceptible to risk and unpredictability in terms of results and profitability. In Noelbaki Village, Central Kupang, Kupang. This study intends to examine income, income risk, and factors that influence lowland rice farming income risk. To identify 46 respondents, the sample was determined using a basic random sampling procedure. Primary data was acquired through interviews and a questionnaire for this study. The income function model's input-output methodology, coefficient of variation (CV), and residual squared are used in data analysis. The average value of income in lowland rice cultivation per hectare each growing season was Rp. 28,374,581,-/ha/MT, according to the findings. The CV score of 3.26 percent indicates the average amount of income risk in lowland rice growing. Land area, fertilizers, insecticides, and UPT are elements that minimize income risk, whereas seeds raise income risk. Because seeds dictate the quality of plant development, whereas other production elements may be regulated by farmers, this suggests that seeds are a determinant of income risk. Farmers must pay attention to seed quality if rice growing is to stay risk-free.